Changes in stress-related outcomes among graduate students following the Mindfulness Ambassador Program: A pilot study - Varsha Vasudevan; Benjamin Tran; Shauna M. Burke; Patricia Tucker; Jennifer D. Irwin (PLoS ONE, 2025)
Objectives Graduate students face numerous demands, high stress levels, and associated challenges to intra- and inter-personal relationships. Mindfulness may help to ease such challenging experiences. The Mindfulness Ambassador Program (MAP) is a promising group-based program that has not yet been studied among graduate students. The primary objectives of this study were to: (1) explore graduate students’ perceptions of stress, and their relationships with themselves and meaningful others; (2) explore graduate students’ perspectives of and satisfaction with the MAP; and (3) investigate if participation in the MAP elicited changes in graduate students’ perceived levels of stress, self-awareness, interpersonal skills, and/or social connectedness. Methods In this one-group, pre/post mixed-methods pilot study, nine participants completed pre-post questionnaires and participated in a semi-structured interview post-intervention. Data were analyzed using descriptive statistics, thematic analysis, and paired t-tests. Results Pre-intervention, qualitative themes included participants experiencing moderate-to-high stress levels, intrapersonal conflict, interpersonal relationship challenges, and seeing oneself as a work in progress. Post-intervention themes included better stress management, increased consideration for oneself and others, feelings of connection with others, and overall satisfaction with the MAP. Statistically significant improvements were found from pre- to post-intervention in mean score differences for perceived stress (p = .043), private self-awareness (p = .006), awareness of immediate surroundings (p = .044), and social connectedness (p = .006). Conclusions Participants reported several benefits from their positive experience participating in the MAP. These findings may be used to inform future mindfulness-based programming for graduate students.